Validated specialty‐specific models for multi‐disciplinary microsurgery training laboratories: a systematic review. Issue 6 (15th March 2021) - Crouch, Gareth; Wong, Gerald; Hong, Jonathan; Varey, Alex; Haddad, Roger; Wang, Zane Zhanxiang; Wykes, James; Koutalistras, Nick; Clark, Jonathan R.; Solomon, Michael; Bannon, Paul; McBride, Kate E.; et al.
Abstract: Background: Laboratory simulation is increasingly important for teaching microsurgical skills. Training microsurgeons of different specialties within the same simulation laboratory increases efficiency of resource use. For maximal benefit, simulations should be available for trainees to practice specialty‐specific, higher‐order skills. Selection of appropriate simulations requires knowledge of the efficacy and validity of the numerous described laboratory models. Here we present a systematic review of validated training models that may serve as useful adjuncts to achieving competency in specialty elements of microsurgery, and appraise the evidence behind them. Methods: In setting up a multi‐disciplinary microsurgery training course, we performed a systematic review according to preferred reporting items for systematic reviews and meta‐analyses guidelines. EMBASE, MEDLINE, Cochrane and PubMed databases were searched for studies describing validated, microscope‐based, specialty‐specific simulations, and awarded a level of evidence and level of recommendation based on a modified Oxford Centre for Evidence‐Based Medicine classification. Results: A total of 141 papers describing specialty‐specific microsimulation models were identified, 49 of which included evidence of validation. Eleven were in the field of neurosurgery, 21 in otolaryngology/head and neck surgery, two in urology/gynaecology and 15 plastic and reconstructive surgery. These papers described synthetic models in 19 cases, cadaveric animals in 10 cases, live animals in 12 cases and human cadaveric material in 10 cases. Conclusion: Numerous specialty‐specific models for use in the microscope laboratory are available, but the quality of evidence for them is poor. Provision of models that span numerous specialties may encourage use of a microscope lab whilst still enabling more specific skills training over a 'one‐size‐fits‐all' approach. Abstract : Laboratory simulation is increasingly important for teaching microsurgical skills. Training microsurgeons of different specialties within the same simulation laboratory increases efficiency of resource use. Here we present a systematic review of validated training models that may serve as useful adjuncts to achieving competency in specialty elements of microsurgery, and appraise the evidence behind them.